Social indications (Marriage websites) - A field study in internet cafes - نبراس عدنان المطيري (College of Education for Women, 2019)
Marriage is considered one of the strongest ties that links between two human beings , but after the evolutions that happened in our Arab communities and specifically in the Iraqi community , marriage through the internet websites appeared . this kind of marriage is considered one of the new phenomena that appeared in the present time in many societies. That was through internet websites like yahoo , Facebook and other websites that have chat features. The Islamic sharia looks negatively at marriage through the internet announcing that this way is harmful for both the man and the woman